Length-weight relationship in ten fish species from the Nhamundá River, the Amazon Basin, Brazil - FREITAS, Tiago Magalhães da Silva (Instituto Nacional de Pesquisas da Amazônia, 2020)
Studies on the length-weight relationship (LWR) of fishes are an important tool to describe several biological aspects of the species. Consequently, these studies are relevant due the necessity of comprehension about fish life cycle. Thus, this study aimed to establish the length-weight relationship of the ten most common fish in the Lower Nhamundá River, left tributary of the Amazon River. The capture of fish was conducted in January 2008 using gill nets. A total of 807 individuals, ten species and three Orders (Characiformes, Siluriformes and Clupeiformes) were analyzed. The parameter b varied from 2.680 to 3.698. The LWR were shown for the first time for two species: Anostomoides laticeps and Ageneiosus polystictus. Finally, this research emphasizes the importance of LWR studies in the Amazon and the use of primary data for fisheries management plans.